Perkembangan Usia Dini - Dinda Meirani; Diva Nurhasanah; Misna Misna; Linda Yarni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Early childhood development includes several aspects of socialization, cognitive and moral aspects. The definition is that socialization is the process of learning norms, values ​​and behavior that are in accordance with society's needs. In early childhood, socialization can occur through interactions with adults and friends. Some examples of social development in early childhood are: greeting each other when going out, responding to adults with confidence, expressing affection for other children, taking part in large activities, imitating what children do as adults, and expressing their feelings verbally.